2021
DOI: 10.1088/1755-1315/892/1/012109
|View full text |Cite
|
Sign up to set email alerts
|

Food waste handling perception in Indonesia: communicating the sustainability of Food and environment

Abstract: Every week, Indonesia discards approximately 10 million pieces of bread, cakes, and cookies, equating to 292,000 tons of CO2 emissions similar to Indonesia’s annual CO2 emissions. Due to a lack of resources and infrastructure, most impoverished countries rely on antiquated technologies such as anaerobic digestion (AD) to handle food waste. Bakery trash is a biologically formed organic waste that poses a serious threat to public health and the environment, including natural ecosystem contamination. The goal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…Meanwhile, almost 33% of respondents are already aware of the harm posed by food waste but have chosen to disregard the seriousness of the situation. This suggests that just 48 per cent of respondents are aware of the problem of food waste and , where the majority of Indonesian did not aware of the danger of Food waste [4]. The majority of Southeast Asian people being aware are dominated by Singaporeans (where more than 65% of the Singaporean respondents, are aware of the dangers of food waste into environmental).…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, almost 33% of respondents are already aware of the harm posed by food waste but have chosen to disregard the seriousness of the situation. This suggests that just 48 per cent of respondents are aware of the problem of food waste and , where the majority of Indonesian did not aware of the danger of Food waste [4]. The majority of Southeast Asian people being aware are dominated by Singaporeans (where more than 65% of the Singaporean respondents, are aware of the dangers of food waste into environmental).…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…Taking into consideration all available facts, it can be concluded that as the overall quantity of garbage created by each family type increases, so does the carbon footprint and the amount of revenue earned by each family home in Southeast Asia. In an effort to accelerate the awareness of Food Waste Recycling Management, the media plays the role of a game-changer and pressures the government to create policies related to food waste handling [4], [6]. Meanwhile, most of the respondents (61%) never got sufficient information from the media related to food waste handling (See Figure 3).…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations